2015
DOI: 10.1002/chem.201501037
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Silica Nanoparticles with Multivalent Inhibitory Effects towards Carbonic Anhydrases

Abstract: Multifunctional silica nanoparticles decorated with fluorescent and sulfonamide carbonic anhydrase (CA) inhibitors were prepared and investigated as multivalent enzyme inhibitors against the cytosolic isoforms hCA I and II and the transmembrane tumor-associated ones hCA IX and XII. Excellent inhibitory effects were observed with these nanoparticles, with KI values in the low nanomolar range (6.2-0.67 nM) against all tested isozymes. A significant multivalency effect was seen for the inhibition of the monomeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…It should be mentioned that many CAs are monomeric enzymes, but some of them are also dimers, or higher oligomers (dimers, tetramers, etc.). [13] The results showeda ni ncrease of inhibitory potency (low nanomolar activity,a sp reviously observed with gold nanoparticles), [14] but also as pecific multivalency effect against the cytosolici soforms hCA Ia nd hCA II versust he transmembrane isoforms hCA IX and hCA XII. By catalyzing the interconversion of CO 2 and the bicarbonate ion, the twelve catalytically active isoforms found in humans are involvedi nn umerousp hysiological processes such as respiration, pH regulation, and fluid formation.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…It should be mentioned that many CAs are monomeric enzymes, but some of them are also dimers, or higher oligomers (dimers, tetramers, etc.). [13] The results showeda ni ncrease of inhibitory potency (low nanomolar activity,a sp reviously observed with gold nanoparticles), [14] but also as pecific multivalency effect against the cytosolici soforms hCA Ia nd hCA II versust he transmembrane isoforms hCA IX and hCA XII. By catalyzing the interconversion of CO 2 and the bicarbonate ion, the twelve catalytically active isoforms found in humans are involvedi nn umerousp hysiological processes such as respiration, pH regulation, and fluid formation.…”
Section: Introductionmentioning
confidence: 79%
“…Here, we report the design, synthesis, and evaluation of multivalent inhibitors of carbonic anhydrases (CAs, EC 4.2.1.1) that are effectively obtained by using bioconjugation techniques. We previously used fluorescent silica nanoparticles coated with multiple copies (12)(13)(14)(15) of sulfonamide-based CA inhibitors. [5] Indeed, the CAs are widespread zinc metalloproteins in higherv ertebrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another way to activate such inhibitors is to bind them to polymers or nanostructures to create multiple binding sites . The modification of fullerene with an iminosugar, which is an inhibitor for Jack bean α‐mannosidase, leads to 179 times higher activity of this inhibitor .…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Another way to activate such inhibitors is to bind them to polymers or nanostructures to create multiple binding sites. [3,4] The modification of fullerene with an iminosugar,w hich is an inhibitor for Jack bean a-mannosidase, leads to 179 times higher activity of this inhibitor. [5] Bonduelle et al have shown that aggregates of iminosugar-based glycopolypeptides form aggregates that increase the activity of the iminosugars as inhibitors for a-mannosidase by af actor of 30.…”
Section: Introductionmentioning
confidence: 99%